1991
DOI: 10.1038/jcbfm.1991.143
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Oxygen Metabolism after Aneurysmal Subarachnoid Hemorrhage

Abstract: Previous studies of cerebral oxygen metabolism and extraction in patients with subarachnoid hemorrhage (SAH) have yielded conflicting results. We used positron emission tomography (PET) to measure the regional cerebral metabolic rate for oxygen (rCMRO2), oxygen extraction fraction (rOEF), and cerebral blood flow (rCBF) 16 times in 11 patients with aneurysmal SAH. All studies were performed preoperatively; no patient had hydrocephalus or intracerebral hematoma on brain CT. Eight patients with no arteriographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
71
2
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 132 publications
(89 citation statements)
references
References 31 publications
14
71
2
2
Order By: Relevance
“…This finding supports the hypothesis of a metabolic depression and an uncoupling of CBF and oxidative metabolism and is in accordance with data about cerebral perfusion and metabolism gathered previously by patient studies (Carpenter et al, 1991;Martin et al, 1984;Jakobsen et al, 1990;Voldby et al, 1985). Carpenter et al performed early positron emission tomography studies in SAH patients before aneurysm surgery and observed a significant 25% decrease of CMRO 2 even if patients had no signs of vasospasm in angiograms, suggesting a primary metabolic alteration and uncoupling of CBF and metabolism after SAH (Carpenter et al, 1991). However, in these studies, patients were not examined in the first hours after SAH.…”
Section: Brain Tissue Oxygenationsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding supports the hypothesis of a metabolic depression and an uncoupling of CBF and oxidative metabolism and is in accordance with data about cerebral perfusion and metabolism gathered previously by patient studies (Carpenter et al, 1991;Martin et al, 1984;Jakobsen et al, 1990;Voldby et al, 1985). Carpenter et al performed early positron emission tomography studies in SAH patients before aneurysm surgery and observed a significant 25% decrease of CMRO 2 even if patients had no signs of vasospasm in angiograms, suggesting a primary metabolic alteration and uncoupling of CBF and metabolism after SAH (Carpenter et al, 1991). However, in these studies, patients were not examined in the first hours after SAH.…”
Section: Brain Tissue Oxygenationsupporting
confidence: 93%
“…Voldby et al found a concomitant decrease of CMRO 2 with arterial caliber, indicating secondary metabolic impairment due to cerebral vasospasm (Voldby et al, 1985). Other authors did not observe an additional depression of CMRO 2 with the appearance of delayed vasospasm and advocated a primary reduction of metabolism by SAH (Grubb et al, 1977;Carpenter et al, 1991;Frykholm et al, 2004). All of these studies, however, measured CBF and metabolic parameters in patients at various times after SAH and after hospital admission.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze the fitted parameters we compare them to gold standard readings from PET studies. OEF is known to be approximately constant across the healthy brain, with quoted average values typically in the range 35%-43% (26,27). This is borne out by the results in Fig.…”
Section: Discussionmentioning
confidence: 70%
“…There is, however, no established average of vCBV with which we may compare our results. CBV values from PET studies of the healthy brain are typically in the range 3%-4.5% (26,27). Deoxygenated blood is thought to account for the majority of this, but the exact percentage is unknown.…”
Section: Discussionmentioning
confidence: 99%